Differential Levels and Biological Roles of eNOS and SCUBE1 in Endothelial Dysfunction: A Systematic Review - Ali, Hirowati; Rahmadian, Rizki; Rasya, Salsabila Faiha Wiendra; Siregar, Muhammad Abi Ghoffari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Endothelial dysfunction (ED) is a systemic disorder marked by impaired nitric oxide (NO) availability, which is essential for maintaining vascular tone and managing oxidative stress. This dysfunction contributes to vascular pathologies such as atherosclerosis and coronary artery disease (CAD) by fostering vasoconstriction, increased permeability, and inflammatory responses, thereby highlighting the urgent need for biomarkers and interventions aimed at mitigating endothelial dysfunction and its associated risks. The relationship between eNOS and SCUBE1 relates to endothelial function and oxidative stress. This study seeks to clarify the benefits and drawbacks of each biomarker in its capacity as a preventive strategy against endothelial dysfunction. This systematic review, adhering to the PRISMA Checklist, examines evidence on the role of endothelial function and oxidative stress in endothelial dysfunction, with emphasis on the biomarkers eNOS and SCUBE1. Literature searches were conducted in PubMed, ScienceDirect, and Google Scholar, and study quality was appraised based on reported biomarker values and relevance. There were 8 articles with increased eNOS and decreased ROS in several treatments, associated with prevention of endothelial dysfunction. There were 6 articles with increased SCUBE1 in several diseases (breast cancer, STEMI, hashimoto's thyroiditis, peripheral ischemic, pulmonary arterial hypertension, atherosclerosis) being markers of endothelial dysfunction. Both biomarkers can work well according to their release pathways, they can be novel biomarkers of endothelial dysfunction in various diseases. Their main role is on endothelial function, SCUBE1 controls BMPR2 signaling (angiogenic, proliferation, apoptosis) and eNOS focuses on endothelial health through NO production (vasodilation, maintaining vascular tone).